Upaya Mempertahankan dan Meningkatkan Nilai Gizi dan Nilai Organoleptis Pangan Hasil Laut Melalui Teknologi Pengolahan Ikan - Muhammad Danial; Muhammad Tawil; . Wahidah (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2012)
DOWNLOAD PDFThe research aims were: (1) obtained fish fumigator specification which effective to applied in coastal area, (2) high organoleptic value, and (3) rich nutrient content, and longtime period of expire of product. The method consisted designing, making fish crackers, and testing of equipment specification, testing the organoleptic and nutrient value, as well as expired period of the product. Tool specification prototype obtained  from this research were: dryer equipment performance were tetrahedral (175x60x50 cm), Tin 65oC, Tout 60oC, equipment  capacity 30 kg, effectively 55,13%, time of drying 4 hours, fuel volume 3 liter. Product specification are taste like=5, and high nutrient, Fumigator equipment performance are  tetrahedral (165x60x50 cm), Tin 60oC, Tout 55oC, equipment capacity 30 kg, effectively 36,50%, time of drying 3 hours, fuel (charcoal) volume 7 kg. Product specification are high nutrient, organoleptics value very like=6, , and product expired periods 4-5 days.   Key words: Fish technology, nutrient, organoleptic